Reliability and availability of cloud computing - Bauer, Eric.; Adams, Randee; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley-IEEE Press, 2012)
'The book is intended for IS/IT system and solution architects, developers and engineers, as well as technical sales, product management, and quality management professionals'--
Basics. Cloud Computing -- Virtualization -- Service Reliability and Service Availability -- Analysis. Analyzing Cloud Reliability and Availability -- Reliability Analysis of Virtualization -- Hardware Reliability, Virtualization, and Service Availability -- Capacity and Elasticity -- Service Orchestration Analysis -- Geographic Distribution, Georedundancy, and Disaster Recovery -- Recommendations. Applications, Solutions, and Accountability -- Recommendations for Architecting a Reliable System -- Design for Reliability of Virtualized Applications -- Design for Reliability of Cloud Solutions -- Summary.
Includes bibliographical references and index.
Print version record.
Keywords: Cloud computing; Computer software -- Reliability; Computer software -- Quality control; Computer security; Electronic books; Electronic books